Physiology of the Right Ventricle Across the Lifespan - Woulfe, Kathleen C.; Walker, Lori A. (Frontiers in Physiology, 2021)
The most common cause of heart failure in the United States is ischemic left heart disease; accordingly, a vast amount of work has been done to elucidate the molecular mechanisms underlying pathologies of the left ventricle (LV) as a general model of heart failure. Until recently, little attention has been paid to the right ventricle (RV) and it has commonly been thought that the mechanical and biochemical properties of the RV are similar to those of the LV. However, therapies used to treat LV failure often fail to improve ventricular function in RV failure underscoring the need to better understand the unique physiologic and pathophysiologic properties of the RV. Importantly, hemodynamic stresses (such as pressure overload) often underlie right heart failure further differentiating RV failure as unique from LV failure. There are significant structural, mechanical, and biochemical properties distinctive to the RV that influence its function and it is likely that adaptations of the RV occur uniquely across the lifespan. We have previously reviewed the adult RV compared to the LV but there is little known about differences in the pediatric or aged RV. Accordingly, in this mini-review, we will examine the subtle distinctions between the RV and LV that are maintained physiologically across the lifespan and will highlight significant knowledge gaps in our understanding of pediatric and aging RV. Consideration of how RV function is altered in different disease states in an age-specific manner may enable us to define RV function in health and importantly, in response to pathology.